Amphiregulin Regulates Melanocytic Senescence - Pommer, Michaela; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2021)
Oncogene-induced senescence (OIS) is a decisive process to suppress tumor development, but the molecular details of OIS are still under investigation. Using an established OIS model of primary melanocytes transduced with BRAF V600E and compared to control cells, amphiregulin (AREG) was shown to be induced. In addition, AREG expression was observed in nevi, which by definition, are senescent cell clusters, compared to melanocytes. Interestingly, treatment of melanocytes with recombinant AREG did induce senescence. This led to the assumption that extracellular AREG has an important function in this process. Inhibition of the epidermal growth factor receptor (EGFR) using Gefitinib identified AREG as one of EGFR ligands responsible for senescence. Furthermore, depletion of AREG expression in senescent BRAF V600E melanocytes resulted in a significant reduction of senescent melanocytes. This study reveals AREG as an essential molecular component of signaling pathways leading to senescence in melanocytes.
CRIS-Team Scopus Importer:2021-03-05
Keywords: amphiregulin; AREG; normal human primary melanocytes; OIS; oncogene induced senescence